2020
DOI: 10.1039/d0ob00403k
|View full text |Cite
|
Sign up to set email alerts
|

Maleimide-based metal-free ligation with dienes: a comparative study

Abstract: Maleimide-based Diels–Alder strategies for bioconjugation are compared in terms of dienes accessibility and stability, reactions rates, as well as products isolation and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…82 In this context, recent studies from our group have shown that switching to linear diene such as trans-trans-2,4-hexadiene, the maleimide-based cycloaddition proceeded with a second-order kinetic rate constant in the range amenable for KTGS, namely 10 -3 M -1 s -1 . 26 This experimental value shows that maleimide/hexadiene pair would be suitable for KTGS applications, in particular with biological targets that do not contain free cysteine residues, the latter being likely to react with maleimides.…”
Section: Clues For Expanding the Repertoire Of Ktgs Reactionsmentioning
confidence: 89%
See 1 more Smart Citation
“…82 In this context, recent studies from our group have shown that switching to linear diene such as trans-trans-2,4-hexadiene, the maleimide-based cycloaddition proceeded with a second-order kinetic rate constant in the range amenable for KTGS, namely 10 -3 M -1 s -1 . 26 This experimental value shows that maleimide/hexadiene pair would be suitable for KTGS applications, in particular with biological targets that do not contain free cysteine residues, the latter being likely to react with maleimides.…”
Section: Clues For Expanding the Repertoire Of Ktgs Reactionsmentioning
confidence: 89%
“…However, these are two distinct classes of reactions. Bioorthogonal reactions are defined as chemical reactions that can proceed in biological media without interfering with natural chemical functions, while bioconjugation reactions involve chemical functions (generally electrophilic systems) that react with naturally occurring functional groups (such as amines or sulfhydryl moieties). , With the advent of bioorthogonal and bioconjugate chemistry, in recent years, an increasing number of experimental and theoretical studies , and computational analysis on rate constants of such chemical reactions have been made available to the scientific community. Accordingly, in light of reported ligation reactions for biorthogonal ligation or bioconjugation, a nonexhaustive list of new reactions amenable to KTGS strategies will be proposed (Figure A), as well as clues to tune the kinetics of these reaction to increase their potential to meet the requirements for use in KTGS strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A solution of compound 3 (186.3 mg, 0.228 mmol) in a mixture of AcSH/pyridine/CHCl3 (0.8 mL/0.6 mL/0.8 mL) was stirred at room temperature for 20 h. After the completion of the reaction as monitored by TLC, the resulting mixture was concentrated and subjected to flash chromatography on silica gel (hexanes/Acetone = 4:1~1:1) to afford compound 4 (154.8 mg, 82%) as colorless syrup. Rf = 0.25 (hexanes/Acetone = 1:1); 1 H NMR (400 MHz, CDCl3) δ 7.36-7.28 (25H, m, Ar-H), 5.64 (1H, d, J = 7.7 Hz), 5.02-4.95 (3H, m), 4.92 (1H, d, PhCH2, J = 11.9 Hz), 4.86 (1H, d, PhCH2, J = 11.2 Hz), 4.68 (1H, d, PhCH2, J = 12.0 Hz), 4.65-4.57 (5H, m), 4.52 (1H, d, PhCH2, J = 12.0 Hz), 4.20 (1H, dd, J = 8.5 Hz, J = 8.5 Hz), 3.93 (1H, dd, J = 8.2 Hz, J = 8.2 Hz), 3.83-3.65 (5H, m), 3.56-3.44 (4H, m), 3.14 (1H, m), 2.33 (1H, d, J = 8.7 Hz), 1.98 (1H, m), 1.80 (3H, s); 13 To a solution of compound 4 (79.0 mg, 0.095 mmol) and the tosylate linker [2] (125 mg, 0.379 mmol) in anhydrous DMF (3.0 mL) was added 60% sodium hydride (19.0 mg, 0.474 mmol) at 0 °C. After stirring for 0.5 hour at 0 °C then 7.5 hours at room temperature, MeOH (100 µL) and AcOH (25 µL) was added to the reaction mixture at 0 °C.…”
Section: Benzyl 24-di-o-benzyl-β-d-mannopyranosyl-(1→4)-2-azido-36-di-o-benzyl-2-deoxy-β-dglucopyranoside (3)mentioning
confidence: 99%
“…A solution of compound 8 (133.5 mg, 0.142 mmol) in a mixture of AcSH/pyridine/CHCl3 (0.8 mL/0.6 mL/0.8 mL) was stirred at room temperature for 18 h. After the completion of the reaction as monitored by TLC, the resulting mixture was concentrated and subjected to flash chromatography on silica gel (hexanes/EtOAc = 4:1~3:2) to afford compound 9 (113.8 mg, 84%) as colorless syrup. Rf = 0.30 (hexanes/EtOAc = 2:1); To a solution of compound 9 (88.0 mg, 0.092 mmol) and the tosylate linker [2] (76 mg, 0.231 mmol) in anhydrous DMF (2.4 mL) was added 60% sodium hydride (18.5 mg, 0.461 mmol) at 0 °C. After stirring for 0.5 hour at 0 °C then 6 hours at room temperature, MeOH (100 µL) and AcOH (25 µL) was added to the reaction mixture at 0 °C.…”
Section: Benzyl 24-di-o-benzyl-3-o-p-methoxybenzyl-β-d-mannopyranosyl-(1→4)-2-acetamido-36-di-o-benzyl-2-deoxy-β-d-glucopyranoside (9)mentioning
confidence: 99%
See 1 more Smart Citation